Searching for topological dark matter in LIGO data - Heisenberg, Lavinia; Maibach, David; Veske, Doğa (Physical review, 2024)
Gravitational-wave interferometers have been recently proposed as a promising probe in searches for dark matter. These highly sensitive instruments are potentially able to detect the interactions of dark matter with the detector’s hardware. In this work, we explore the possibilities of discovering topological dark matter with the LIGO detectors. We analyze domain walls consisting of dark matter passing through the Earth, leaving traces in multiple detectors simultaneously. Considering dark matter interactions with light in the interferometer, and with the beam splitter, we perform the first analysis of topological dark matter with gravitational-wave strain data. We examine whether astrophysically unexpected triggers could be explained by domain-wall passages. We find that all of the binary black hole mergers we analyze favor the binary black hole merger hypothesis rather than the domain-wall hypothesis, with the closest being GW190521. Moreover, we find that some topological dark matter signals can be caught by binary black hole searches. Finally, we find that special types of glitches in the measurement data can inevitably limit the dark matter searches for certain parameters. These results are expected to guide future searches and analyses.